Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph182111434
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risks in Hospitals, Quality of Life, and Quality of Work Life: A Systematic Review

Abstract: This study systematically reviewed the relationship between occupational risks and quality of life (QoL) and quality of work life (QWL) in hospitals. A systematic review was performed according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guide, and the protocol was submitted on the PROSPERO website (CRD 2019127865). The last search was performed in June 2021 by two independent reviewers in the main databases, a gray literature database, and a manual search (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…Investment in the development of the QWL is profitable, as the utilization level of the intangible employee assets is moderate. QWL is associated with organizational performance and productivity (Kesti et al, 2016; Pot & Koningsveld, 2009), occupational stress (de Lira et al, 2021) and burnout (Wang et al, 2019). QWL interventions can influence employee commitment under effective leadership styles (Nanjundeswaraswamy et al 2020); thus, many benefits for the organizational performance could be gained through the development of QWL, where leaders are in a key role.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investment in the development of the QWL is profitable, as the utilization level of the intangible employee assets is moderate. QWL is associated with organizational performance and productivity (Kesti et al, 2016; Pot & Koningsveld, 2009), occupational stress (de Lira et al, 2021) and burnout (Wang et al, 2019). QWL interventions can influence employee commitment under effective leadership styles (Nanjundeswaraswamy et al 2020); thus, many benefits for the organizational performance could be gained through the development of QWL, where leaders are in a key role.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, anxiety related to COVID-19 has been shown to be associated with lower QWL (Aydın et al, 2021). Occupational stress is related to QWL, and managers play a key role in preventing occupational stress through modifying the work environment; this can be achieved by providing opportunities for skill development, enhancing work conditions, developing functions and offering psychological support (de Lira et al, 2021). Improvement of the QWL has been shown to positively impact workforce retention and psychological well-being (Hardjanti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicate a significant association between QNWL and sleep quality, with better QNWL associated with better sleep. Furthermore, research studies indicate an association between workplace hazards, such as noise, ergonomics, and stress, and hospital employees’ perceptions of a low or moderate quality of work life ( 42–44 ). In this regard, the improvement of working processes involving productivity, quality, service delivery, safety, employee morale, and cost control could improve healthcare work environment standards ( 45–48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The organizational climate has long been recognized as one of the risk factors for workers’ health [ 10 , 11 , 12 ]. Comprehensive literature reviews showed that work environment factors highly correlate to employees’ health and well-being [ 13 ] and to quality of life and quality of working life among healthcare workers [ 14 ]. There is strong evidence that low organizational justice, high job strain, high effort/reward imbalance, and low social support may increase the risk for musculoskeletal disorders [ 15 ], and that poor organization of work may be responsible for the emergence of mental and physical health problems [ 16 ], particularly in hospitals, due to the concurrence of workload, psychosocial, and ergonomic factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%